An empirical study of website adoption among Small and Medium Enterprises (SMEs) in Malaysia - Narayanasamy, Kogilah; Santhapparaj, A. S.; Eze, Uchenna Cyril (IBIMA Publishing, 2008)
In Malaysia, SMEs operate in almost every major industry from manufacturing to manufacturing-related services to agriculture and the services sectors. This study examines the gap between the importance perception and implementation of Web Presence as a critical success factor among small and medium enterprises (SMEs) in Malaysia. Data was obtained from 158 entrepreneurs involved in the Malaysian SMEs. Interviews were also carried out with five SMEs to supplement the statistical findings, Paired t-test results revealed significant differences between web site adoption patterns between SMEs in the manufacturing and the service sector. The findings offer useful insights on how a web presence can contribute towards value creation for SMEs.